Real-world diagnostic potential of bacterial biomarkers of canine periodontitis - Wallis, C. V.; Soltero-Rivera, M.; Harvey, C.; Reynolds, R. M.; Carvell-Miller, L. J.; Colyer, A.; McKee, T. S.; Mills, T.; Bergman, P. J.; Watson, P.; Holcombe, L. J. (Frontiers in Veterinary Science, 2024)
The objective of this study was to investigate the diagnostic potential of bacterial biomarkers by comparing the performance of molecular detection assays with clinical assessments of dog's oral health performed by veterinarians. Supragingival and subgingival plaque samples were collected from 127 client-owned dogs, pre-booked for procedures under general anesthesia, visiting veterinary practices in the USA. DNA was extracted and bacterial biomarkers quantified using quantitative polymerase chain reaction. Gingivitis and periodontitis were recorded by a trained clinician using the Weighted Gingivitis Periodontitis Score which involved assessing the buccal surfaces of 18 teeth whilst under general anesthesia. Intraoral dental radiographs of the left and right mandibular first molar teeth were also obtained. These data were then used to establish the diagnostic performance of the molecular assay to detect periodontitis. An initial conscious, visual oral examination performed by the veterinarian identified 67.7% of dogs as having periodontitis, but examination under general anesthesia indicated a higher proportion (86.6%). Analysis of supragingival plaque samples collected by veterinarians from conscious and unconscious dogs demonstrated the assay had an accuracy of 77.7% to 80.9%, a sensitivity of 77.6% to 81.0%, and a specificity of 80.0%. Use of this molecular screening tool in conscious dogs has the potential to improve early periodontal disease detection and support veterinary decision making, ultimately improving the oral health of dogs and consequently their quality of life.